2014
DOI: 10.1021/bi500990v
|View full text |Cite
|
Sign up to set email alerts
|

Formation of G-Quadruplexes in Poly-G Sequences: Structure of a Propeller-Type Parallel-Stranded G-Quadruplex Formed by a G15 Stretch

Abstract: Poly-G sequences are found in different genomes including human and have the potential to form higher-order structures with various applications. Previously, long poly-G sequences were thought to lead to multiple possible ways of G-quadruplex folding, rendering their structural characterization challenging. Here we investigate the structure of G-quadruplexes formed by poly-G sequences d(TTG(n)T), where n = 12 to 19. Our data show the presence of multiple and/or higher-order G-quadruplex structures in most sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 54 publications
10
53
0
Order By: Relevance
“…On the other hand, it has been demonstrated previously that a poly(G) sequence (G 18 ) blocks the 5΄-3΄ exonuclease activity of Xrn1, thus leading to the accumulation of deadenylated and decapped mRNAs (40,41; Supplementary Figure S2). Recent work has shown that a continuous sequence of guanines in DNA manifests proton NMR spectra indicative of higher order structure once the number of Gs reaches 12 or more (forming G-quadruplexes, four-stranded helical structures held together by a guanine core; 42). In this study, we have used one poly(G) sequence that is shorter (G 10 ) than this threshold length, and one that is longer (G 14 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been demonstrated previously that a poly(G) sequence (G 18 ) blocks the 5΄-3΄ exonuclease activity of Xrn1, thus leading to the accumulation of deadenylated and decapped mRNAs (40,41; Supplementary Figure S2). Recent work has shown that a continuous sequence of guanines in DNA manifests proton NMR spectra indicative of higher order structure once the number of Gs reaches 12 or more (forming G-quadruplexes, four-stranded helical structures held together by a guanine core; 42). In this study, we have used one poly(G) sequence that is shorter (G 10 ) than this threshold length, and one that is longer (G 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Poly(G) stretches occur quite widely in diverse genomes in a range of locations (for example in promoters, telomeres and 5΄UTRs; 42,58). The G 14 motif selected for use in this study is likely to have an intermediate propensity to form a stable G-quadruplex structure (42), consistent with its ability to inhibit translation initiation in yeast by approximately 90% (Table 1; Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of muRif1 with characteristic subsets of G4 DNA ~ There are several well known G4 oligonucleotides that have been structurally characterized (38)(39)(40)(41)(42)(43)(44)(45)(46). We used ten of them for EMSA with purified muRif1 (Supplementary Fig.…”
Section: -12)mentioning
confidence: 99%
“…The DNAbinding domain of mammalian Rif1 has been reported to bind to structured DNAs including forked DNA, flap DNA and cruciform structures 31,32 . Therefore, we prepared various structured DNAs and used them in competition assays with the G 24 DNA, which is known to form a parallel-type G-quadruplex structure 33 . In the presence of Rif1 protein, the G-quadruplex G 24 DNA was specifically mobility shifted (Fig.…”
Section: Purified Rif Protein Binds To G-quadruplex Structuresmentioning
confidence: 99%